8 years cohort study on short term outcome of sutureless thyroidectomy in Hospital Raja Perempuan Zainab II - Alias, Am Basheer (2016)
Background: Thyroid surgery is one of the most common surgery performed now days with very low complication rates. The introduction of vessel sealing technology have assisted surgeon in securing hemostasis in limited operative field and shortened the operative time. However, surgeons are still skeptical in using this technology as there are many important structures in close proximity to the thyroid gland. Therefore, this study is performed to evaluate the outcome of sutureless thyroidectomy as compared to conventional knot tying technique. Methods: This is a retrospective cohort study of case record of patients who underwent total thyroidectomy from 1st January 2007 to 31st December 2014 in Hospital Raja Perempuan Zainab II, Kota Bharu, Kelantan. Those who met the inclusion criteria will be recruited in the study. Patients were divided into two groups based on conventional or sutureless thyroidectomy. The short term outcome post thyroidectomy were studied. The data were analyzed using Statistical Package for the Social Sciences (SPSS). Results: Total of 495 patients were included in this study aged between 8 and 76 years old with mean age of 44.7(13.29) years. It comprises 70 males and 425 female. Majority were Malays (96.6%), followed by Chinese (2.2%) and Indian (0.4%). From the total of 495 patients, 71 of them underwent sutureless thyroidectomy and 424 patients underwent conventional thyroidectomy. The mean operative time was significantly lower in the sutureless group (100.71 versus 121.73 min, p < 0.01). There were no significant difference in the post-operative outcome of sutureless thyroidectomy compared to conventional thyroidectomy in term of transient hypocalcemia (21.1% versus 25.7%), permanent hypocalcemia (0% versus 3.1%), transient recurrent laryngeal nerve injury (0% versus 2.8%), permanent recurrent laryngeal nerve injury (0% versus 1.4%), hematoma (0% versus 1.2%), reoperation (0% versus 0.2%), surgical site infection (0% versus 0.5%) and tracheostomy (0% versus 0.2%). There were no statistical significant comparing the post-operative length of stay between these 2 groups. Conclusion: Post-operative complications in sutureless thyroidectomy were similar if not better than conventional thyroidectomy. Therefore, sutureless thyroidectomy can be safely practiced as it have the advantage of shorter operative time thus indirectly improving the operating room efficiency.